زوائد رجال مسند الإمام الحميدي على الكتب الستة: جمع ودراسة - فرج، إسلام سمير محمد (جامعة الأزهر - كلية اصول الدين والدعوة باسيوط, 2019)
زوائد رجال مسند الإمام الحميدي على الكتب الستة جمع ودراسة" إسلام سمير محمد فرج قسم الحديث وعلومه، كلية البنات الإسلامية بأسيوط، جامعة الأزهر، مصر البريد الإلكتروني: islam.farag@azhar.edu.eg إن خدمة السنة النبوية والدفاع عنها من أعظم الأعمال وأفضل القربات، وقد نشط أهل الحديث لذلك أيما نشاط، فصنفوا العلوم، ودونوا الدواوين، وكان من ثمار جهودهم المباركة علم الزوائد، فتتطرق البحث إلى الكلام عن علم الزوائد، وهو على قسمين: الأول: زوائد المتون: وهو إفراد ما زاد من متون مصنف على متون الكتب الستة أو زيادة عليها، أو غيرها. الثاني: زوائد الرجال: وهو إفراد زوائد رجال مصنف على رجال الكتب الستة أو زيادة عليها، أو غيرها. ووقع اختياري في هذا البحث على كتاب المسند للإمام الحميدي لإفراد زوائد رجاله على رجال الكتب الستة، والبحث فيه عن أحوال رواته الذين انفرد بهم، ومعرفة ما قيل فيهم من جرح وتعديل، ثم تطرقت في نهاية البحث إلى الحديث عن المبهمات الواردة في المسند، فجمعت مبهمات الأسانيد الموجودة في المسند زائدة على ما في الكتب الستة. وأما ما توصلت إليه من نتائج فهو: أهمية إفراد زوائد رجال هذا الكتاب تيسيرا على الباحثين في دراسة أسانيده.
The service and defense of the Prophet's Sunnah is one of the greatest deeds and worships, the scientists of Hadith were very active in that field, they classified the sciences and they wrote the books. the science of Zawaed Al-Hadith was one of the blessed efforts in that field. The research sheds light on the science of Zawaed Al-Hadith, which is in two parts: the first: Zawaed of Matn (Matn is the text of the Hadith), those are Ahadith that are not existent in the Six Books ( authentic books of Hadith) or the others. The second: Zawaed of narrators: those are narrators that are not existent in the Six Books or the others. The research sheds light on one of the Hadith book which is The Musnad by Imam Al-Humaidy to single out its narrators over the narrators of the Six Books, to show the conditions of its narrators and also, to show what was said about them. At the end of the research, it was shown the ambiguities in The Musnad, so the research has gathered the ambiguous narrators that in The Musnad, that are not existent in the Six Books, and the research has found out the following: The importance of showing the narrators of the Musnad that helps the research in studying its narrators
Keywords: السنة النبوية -- أهل الحديث -- الإمام الحميدى، الحميدي عبدالله بن الزبير بن عيسى بن عبيدالله، ت. 834 م